The relationship between occupational exposures and history of preterm birth in operating room staff and nursing wards of Isfahan teaching hospitals: a retrospective study - Faride Ansari; Leila Akbari; Shahnaz Kohan (Mashhad University of Medical Sciences, 2019)
Introduction: Nurses and staff of operating room are exposed to several occupational exposures; some of these exposures may have adverse influences on their reproductive health. Therefore, this study was performed with aim to evaluate occupational exposures and preterm birth history in operating room staff and nursing wards of Isfahan teaching hospitals. Methods: This descriptive study was performed on 300 women working in nursing wards and operating room of Isfahan educational hospitals in 2017 to 2018. Data collection tool was a questionnaire. The questionnaire included demographic and fertility information, occupational status, and adverse pregnancy outcomes during the last pregnancy. Data were analyzed by SPSS software (version 16) and T-test, Chi-square and Mann-Whitney tests. PResults: In this study, 29 (19.3%) of women working in operating room and 24 (16%) of women working in nursing wards had a history of preterm delivery at last pregnancy that was not significantly different (P = 0.45). 111 operating room staff (74%) experienced more than 3 hours of standing and 42 (28.1%) experienced over 44 hours of work per week. The operating room group was more exposed to anesthetic gases, sterilizing agents, and stressful environments that was statistically significant (P< 0.05). Despite the difference in most adverse occupational situations, no statistically significant difference was found between two groups in terms of preterm delivery risk (P = 0.45). Conclusion: Regarding the frequency of undesirable occupational situations in both groups, especially the operation room group, no significant difference was found between two groups in the incidence of preterm labor. Therefore, it is suggested that a similar study be carried out with a larger sample size and, if possible, at national level and as a prospective cohort.